4(1H)-Pyridone and 4(1H)-Quinolone Derivatives as Antimalarials with Erythrocytic, Exoerythrocytic, and Transmission Blocking Activities - Monastyrskyi, Andrii; E. Kyle, Dennis; Manetsch, Roman (Current Topics in Medicinal Chemistry, 2014)
Infectious diseases are the second leading cause of deaths in the world with malaria being responsible for approximately the same amount of deaths as cancer in 2012. Despite the success in malaria prevention and control measures decreasing the disease mortality rate by 45% since 2000, the development of single-dose therapeutics with radical cure potential is required to completely eradicate this deadly condition. Targeting multiple stages of the malaria parasite is becoming a primary requirement for new candidates in antimalarial drug discovery and development. Recently, 4(1H)- pyridone, 4(1H)-quinolone, 1,2,3,4-tetrahydroacridone, and phenoxyethoxy-4(1H)-quinolone chemotypes have been shown to be antimalarials with blood stage activity, liver stage activity, and transmission blocking activity. Advancements in structure-activity relationship and structure-property relationship studies, biological evaluation in vitro and in vivo, as well as pharmacokinetics of the 4(1H)-pyridone and 4(1H)-quinolone chemotypes are discussed.
Keywords: 2